On the Order of Convergence and the Dynamics of Werner-King's Method (Contemporary Mathematics, 2023)
In this paper, we present the local convergence analysis of Werner-King's method to approximate the solution of a nonlinear equation in Banach spaces. We establish the local convergence theorem under conditions on the first and second Fréchet derivatives of the operator involved. The convergence analysis is not based on the Taylor expansions as in the earlier studies (which require the assumptions on the third order Fréchet derivative of the operator involved). Thus our analysis extends the applicability of Werner-King's method. We illustrate our results with numerical examples. Moreover, the dynamics and the basins of attraction are developed and demonstrated.
Keywords: Werner-King's Method, Taylor expansion, Fréchet derivative, order of convergence